Praktyka przeprowadzania interwencji dewizowych a ich skuteczność - Franek, Sławomir (The Practice of Foreign Exchange Interventions and Their Effectiveness, 2006)
This article discusses the role of foreign exchange interventions especially in the inflation targeting regime, focusing on the Polish perspectives. The article describes several methods by which interventions can be conducted. The analysis offers guidance on the operational aspects of official intervention, particularly in the aspect of the objectives, choice of markets and counterparties, amount and timing. Special attention is given to the effectiveness and credibility of central banks' FX interventions
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 222-230